Analisis Pembayaran Premi Dalam Asuransi Jiwa Pada PT. Sunlife Financial Cabang Kota Medan - Nur Marpaung, Deri Arifin; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Premium is a sum of money paid by the insured to the insurer (insurance company) whose amount has been determined, in order to protect the possibility of an unwanted risk in the future. The problem involved in this study is life insurance because life insurance takes into account Life Protection or takes into account when a person will die and can survive it is necessary an analysis related to time. This type of research is field using qualitative descriptive method. The research subject is PT.Sunlife Financial Medan City Branch. The primary data in the form of information related to the calculation of insurance product premiums, market segmentation applied to certain products and financial statement data of insurance companies in accordance with the products offered.Referring to some of the policies presented, the price of Sun Life insurance premiums starts from Rp.90-Rp.270 thousands per month. The whole concept of insurance requires its participants to make regular payments or make insurance contributions called as insurance premiums.